The whole is greater than the sum of its parts: Pricing pressure indices for mergers of vertically integrated firms - Michael Trost (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
The paper analyzes gross upward pricing pressure indices called iGUPPI to assess the effects of a merger between vertically integrated firms where in the downstream market also independent rivals are active. Such indices could be used e.g. to screen mergers between mobile network operators which compete with mobile virtual network operators in the downstream retail market. It is shown that the iGUPPI for the downstream market corresponds to the sum of two well-known upward pricing pressure indices, the GUPPI concept of Salop/Moresi (2009) and the vGUPPI concept of Moresi/Salop (2013). Such a simple decomposition however does not hold for the upstream market a priori. Here, additional effects arise which are not included by the two concepts. Further assumptions on the price reactions of the downstream divisions to increases in the input prices are imposed so that the iGUPPI for the upstream market allows for a decomposition into an upstream market version of the GUPPI and the vGUPPI.
urn:nbn:de:bsz:100-opus-14797
Keywords: L41; L42; 330; pricing pressure indices; vertically integrated firms; mergers; UPP; GUPPI; vGUPPI